A comparative evaluation of state-of-the-art approaches for web service composition - Tabatabaei, Sayed Gholam Hassan; Wan Kadir, Wan Mohd. Nasir; Ibrahim, Suhaimi (2008)
In today's Web environment, many enterprises decide to implement and publish their applications on the Internet using Web services technology. In many cases, a single service is not sufficient to fulfill the user's request. To solve this problem, services should be combined together. Therefore, composition of Web services is one of the recent critical issues. A number of approaches have been presented, to tackle this problem. In this paper, we categorize these approaches into four categories (Workflow-based, Al-planning based, Syntactic-based, and Semantic-based). Then, we compare these approaches based on some criteria (like QoS, scalability, and correctness). Investigation of that classification will help researchers who are working on service composition to deliver more applicable solutions.